Influence of the ethylene‐related signal‐inhibiting octapeptide NOP‐1 on postharvest ripening and quality of 'Golden Delicious' apples. (25th February 2019) - Klein, Simone; Fiebig, Antje; Neuwald, Daniel; Dluhosch, Dominik; Müller, Lena; Groth, Georg; Noga, Georg; Hunsche, Mauricio
Abstract: BACKGROUND: Processes extending the shelf life of climacteric fruit play an important role in terms of a sustainable global food supply. In a previous study, a synthetic octapeptide (NOP‐1) was shown to inhibit the interaction between ethylene receptor (ETR) and ethylene insensitive‐2 (EIN2), and in consequence delay tomato ripening. We investigated for the first time the effect of NOP‐1 on inhibiting the ripening of apples ('Golden Delicious') during postharvest. RESULTS: Using purified recombinant proteins from a bacterial expression system, we demonstrate here that EIN2 also interacts tightly ( K d = 136 ± 29 nmol L −1 ) with the corresponding apple ETR MdETR1. In line with previous binding studies on tomato ETRs, the ripening‐delaying peptide NOP‐1 clearly binds to the purified apple ETR. An NOP‐1 solution (1000 µmol L −1 ) was applied with a brush or microdispenser and compared with apples treated with 1‐methylcyclopropene (1‐MCP) (SmartFresh™, Agrofresh) applied as gaseous treatment or untreated control fruits. NOP‐1 inhibited colour development and chlorophyll degradation during shelf life. These effects were more pronounced with the brush application (surface film) than with microdroplets application (mimicking a sprayable formulation). NOP‐1 did not alter ethylene release or respiration rate, whereas 1‐MCP expectedly strongly suppressed both. There were no differences in quality parameters evaluated. CONCLUSION: Our study shows that NOP‐1 binds to MdETR1 which results in delaying of ethylene‐dependent ripening developments of skin colour and chlorophyll. Besides application methods, possible reasons for the weak effect of NOP‐1 in comparison with previous tomato experiments could be different receptor affinity and penetration differences. © 2019 Society of Chemical Industry